Patient voice in metastatic cancer: A conceptual analysis. Issue 6 (13th October 2022) - Kaler, Abbey; Johnson, Constance; Whisenant, Meagan
Abstract: Aim: To analyze the concept of patient voice and discuss implications for clinical care of individuals with metastatic cancer. Background: The diagnosis of metastatic cancer requires increased patient support and healthcare resource utilization. The patient voice should be heard and incorporated into care planning to improve the overall experience of individual with metastatic cancer. Design: Concept analysis. Data sources: Dictionary definitions and scientific literature from electronic databases, including PubMed. Review methods: Using Walker and Avant's method of concept analysis, we identified attributes, antecedents, and consequences. Results: Patient voice is defined as verbal or written communication by the patient to their healthcare partner to positively influence their quantity and quality of life. Attributes of patient voice include context, healthcare partner, safety, time, active listening, communication, and incorporation. Antecedents to patient voice include patient, baseline knowledge, continuing education, medical system culture, and emotional intelligence, and consequences include improved quality of life, adherence to treatment plan, overall satisfaction, and sense of control. Every instance of patient voice prepares the individual for future experiences that can positively impact their care. Conclusions: The concept of patient voice is vital to integrate into care to ensure individual's wishes and goals are incorporated in advanced disease populations. Systematically incorporating the patient voice into the care of individuals with metastatic cancer will allow patients to experience treatment and the progression to end‐of‐life care according to their preferences.